An Angel by my Side : Amazing True Stories of the Afterlife - Jacky Newcomb (London HarperCollins Publishers, 2006)
A collection of true stories of communication with those in the afterlife, this book includes real-life rescues, mysterious dream visitations, near death experiences and miraculous recoveries.
Keywords: Near-death experiences -- Future life